International communication - Anokwa, Kwadwo (Wadsworth/Thomson Learning, 2003)
This edited volume of 16 readings is a collection of works from the foremost scholars of international communication. Divided into seven parts, the text is comprehensive in its coverage, including perspectives on issues and topics such as press freedom, propaganda, gatekeeping, colonialism and mass media development, globalization, cultural concerns, and diffusion